2014
DOI: 10.1021/ic5005598
|View full text |Cite
|
Sign up to set email alerts
|

Toward Coordination Polymers Based on Fine-Tunable Group 13 Organometallic Phthalates

Abstract: A family of group 13 organometallic macrocyclic phthalates [(MMe2)2(μ-O2C)2-1,2-C6H4]2 (where M = Al (1), Ga (2), In (3)) is prepared, and the reactivity of these homologous carboxylates toward various monodentate Lewis bases is investigated. The studies provide the first structurally characterized methylindium [{(Me2In)(μ-O2C)2-1,2-C6H4}{Me2In(THF)}]n (4) and methylaluminum [{(Me2Al)(μ-O2C)2-1,2-C6H4}{Me2Al(py-Me)}]n (5) 1D coordination polymers stabilized by dicarboxylate ligands as a result of disruption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…For example, upon dissolution of a dimeric dichloroaluminium carboxylate [Cl 2 Al(μ-O 2 CR′)] 2 followed by the addition of 4-methylpyridine ( py-Me) a six-coordinate Lewis acid-base adduct [ (where M = Al or In), demonstrated that the dormant Lewis acidity opened a route to the formation of coordination polymers in the presence of Lewis bases (Scheme 1b). 9 In the course of our systematic studies on organometallic carboxylates, 1a we report on the structural investigations of a family of the group 13 [Me 2 M(μ-O 2 CPh)] 2 -type benzoates (where M = B, Al and Ga) to obtain a more in-depth understanding of both the changes in the bonding of group 13 organometallic carboxylate adducts with a pyridine ligand and the mode of dormant Lewis acidity realized for these complexes upon moving from the tetrahedral to higher coordinated moieties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, upon dissolution of a dimeric dichloroaluminium carboxylate [Cl 2 Al(μ-O 2 CR′)] 2 followed by the addition of 4-methylpyridine ( py-Me) a six-coordinate Lewis acid-base adduct [ (where M = Al or In), demonstrated that the dormant Lewis acidity opened a route to the formation of coordination polymers in the presence of Lewis bases (Scheme 1b). 9 In the course of our systematic studies on organometallic carboxylates, 1a we report on the structural investigations of a family of the group 13 [Me 2 M(μ-O 2 CPh)] 2 -type benzoates (where M = B, Al and Ga) to obtain a more in-depth understanding of both the changes in the bonding of group 13 organometallic carboxylate adducts with a pyridine ligand and the mode of dormant Lewis acidity realized for these complexes upon moving from the tetrahedral to higher coordinated moieties.…”
Section: Introductionmentioning
confidence: 99%